Lenalidomide: deciphering mechanisms of action in myeloma, myelodysplastic syndrome and beyond. (December 2015) - Guirguis, Andrew A; Ebert, Benjamin L
Highlights: Lenalidomide modulates substrate specificity of CRL4 CRBN E3 ubiquitin ligase. Ubiquitin ligase substrates include IKZF1/IKZF3 in myeloma and CK1α in del(5q) MDS. In targeting an E3 ubiquitin ligase, IMiDs represent a novel mechanism of action. Additional unidentified substrates likely remain to be identified and characterized. Abstract : Lenalidomide and its related 'analogues' modulate the substrate specificity of the CRL4 CRBN E3 ubiquitin ligase complex. Polyubiquitination and subsequent proteasomal degradation of IKZF1 and IKZF3 in multiple myeloma and CK1α in del(5q) MDS has recently been linked to therapeutic efficacy of this class of compounds. Harnessing ubiquitin ligase substrate specificity, may in time facilitate the degradation of other 'undruggable' proteins and allow for separation of detrimental side effects of IMiD compounds from those associated with therapeutic efficacy.